2010
DOI: 10.1021/jp104814u
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Temperature Influence on the Desorption Pathway of the LiBH4−MgH2 Composite System

Abstract: The decomposition pathway in LiBH4−MgH2 reactive hydride composites was investigated systematically as a function of pressure and temperature. Individual decomposition of MgH2 and LiBH4 is observed at higher temperatures and low pressures (T ≥ 450 °C and p(H2) ≤ 3 bar), whereas simultaneous desorption of H2 from LiBH4 and formation of MgB2 was observed at 400 °C and a hydrogen backpressure of p(H2) = 5 bar. The simultaneous desorption of H2 from LiBH4 and MgH2 without intermediate formation of metallic Mg coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 36 publications
4
120
0
2
Order By: Relevance
“…(Cho et al, 2006) and Barkhordarian et al (Barkordarian et al, 2007) independently discovered that the usage of borides especially MgB 2 as a starting material facilitates the formation of different borohydrides. This finding initiated the development and investigation of several new reversible systems with high storage capacities of 8 -12 wt.% H 2 and improved thermodynamic and kinetic properties such as 2 LiBH 4 +MgH 2 2010;2010b), 2 NaBH 4 +MgH 2 Pistidda et al, 2010;Pottmaier et al, 2011), Ca(BH 4 ) 2 +MgH 2 (Barkhordarian et al, 2008), 6 LiBH 4 +CeH 2 , 6 LiBH 4 +CaH 2 (Jin et al, 2008b), LiBH 4 /Ca(BH 4 ) 2 (Lee et al, 2009 (Bösenberg et al, 2010b) could show that due to a higher thermodynamic driving force for the favoured reaction the competing reactions can be suppressed by applying a hydrogen back pressure and limiting the dehydrogenation temperature. Nevertheless, since long-range diffusion of metal atoms containing species is required, see Fig.…”
Section: Borohydridesmentioning
confidence: 99%
“…(Cho et al, 2006) and Barkhordarian et al (Barkordarian et al, 2007) independently discovered that the usage of borides especially MgB 2 as a starting material facilitates the formation of different borohydrides. This finding initiated the development and investigation of several new reversible systems with high storage capacities of 8 -12 wt.% H 2 and improved thermodynamic and kinetic properties such as 2 LiBH 4 +MgH 2 2010;2010b), 2 NaBH 4 +MgH 2 Pistidda et al, 2010;Pottmaier et al, 2011), Ca(BH 4 ) 2 +MgH 2 (Barkhordarian et al, 2008), 6 LiBH 4 +CeH 2 , 6 LiBH 4 +CaH 2 (Jin et al, 2008b), LiBH 4 /Ca(BH 4 ) 2 (Lee et al, 2009 (Bösenberg et al, 2010b) could show that due to a higher thermodynamic driving force for the favoured reaction the competing reactions can be suppressed by applying a hydrogen back pressure and limiting the dehydrogenation temperature. Nevertheless, since long-range diffusion of metal atoms containing species is required, see Fig.…”
Section: Borohydridesmentioning
confidence: 99%
“…LiBH 4 -YH 3 , [59] LiBH 4 -SrH 2 , [60] and a promising and well-studied composite LiBH 4 -MgH 2 (2:1). [61][62][63] The dehydrogenation mechanism of the latter is investigated with in situ SR-PXD (Figure 4), which reveals a two-step decomposition reaction, i.e. MgH 2 decomposes to form Mg and gaseous H 2 , and finally LiBH 4 and Mg react to form LiH, MgB 2 and H 2 gas.…”
Section: ) Hydrogen Release and Uptake From Reactive Hydride Compositesmentioning
confidence: 99%
“…. [63] Another system which enables hydrogen uptake at relatively benign conditions is the LiBH 4 -MgH 2 -Al system, which recently was investigated in the molar ratios 4:1:1 and 4:1:5. [65] A detailed investigation of the reaction pathway was obtained by in situ SR-PXD measurements, which show interesting differences between the two samples.…”
Section: ) Hydrogen Release and Uptake From Reactive Hydride Compositesmentioning
confidence: 99%
“…More importantly, further research reveals that the dehydriding reaction proceeds by a different mechanism, i.e., MgH 2 and LiBH 4 decompose individually. [25][26][27] The reaction is expressed as follows:…”
Section: Introductionmentioning
confidence: 99%
“…10 It is suggested that low temperature and high hydrogen back pressure (T # 400°C and p(H 2 ) $ 3 bar) should be applied during the dehydrogenation, to avoid the formation of elemental B from the decomposition of LiBH 4 . 26,27 Motivated by these considerations, we have focused on catalyst screening, which is expected to not only lower the dehydrogenation temperature of MgH 2 and LiBH 4 but also promote the formation of MgB 2 compound. It is well known that Ni and Ni-based compounds are good catalysts for lowering the dehydrogenation temperature and enhancing the sorption kinetics of MgH 2 .…”
Section: Introductionmentioning
confidence: 99%